I-fold / Fathul Khaliq Abdul Khairi ... [et al.] - Abdul Khairi, Fathul Khaliq; Azahar, Muhammad Amirul Haqim; Azmi, Muhammad Haziq Hilmi; Aidil, Muhamad Azraf (2017)
The I-Fold is an automatic folding machine which has been improvised from the manual folding board. Nowadays, we have found that many people are so busy to fold their clothes after they have washed it. The i-Fold is the best solution to overcome these problems. After doing some research, we have found that in the market there is a manual folding board that is widely used around the world. Therefore, we came out with the idea to reduce the energy use and time when it comes to folding clothes which is to make this manual folding board fully automated and portable. In addition, we can see that our project will be helpful and useful to others too. It will come in a medium size which is so comfortable for people to use it and the way that our project will be operating is so easy and does not required a high skill to use. The price is affordable and suitable with its good function and aesthetic value. From this project, we hope that our project will be useful to all mankind